Study of amino acids absorption and gut microbiome on consumption of pea protein blended with enzymes-probiotics supplement - Rathi, Abhijit; Gaonkar, Tejal; Dhar, Debojyoti; Kallapura, Gopalakrishna; Jadhav, Swati (Frontiers in Nutrition, 2024)
The current randomized, double-blind, crossover clinical trial was conducted to evaluate changes in the amino acid absorption and gut microbiota on consumption of pea protein supplemented with an enzymes-probiotics blend (Pepzyme Pro). A total of 15 healthy subjects were instructed to take test (pea protein + Pepzyme Pro) or placebo (pea protein + maltodextrin) for 15 days with a 30-day washout period. Blood samples were analyzed for plasma-free amino acids, insulin, and C-reactive protein (CRP). Additionally, nitrogen levels in urine and feces, along with the composition of gut microbiota, were evaluated. On day 15, the test arm showed a tendency to increase the rate of absorption and total absorption (AUC) of amino acids compared with the placebo arm, though the increase was statistically insignificant. In addition, 15-day test supplementation showed a tendency to reduce Tmax of all the amino acids (statistically insignificant except alanine, p = 0.021 and glycine, p = 0.023) in comparison with the placebo supplementation. There were no changes in urine and fecal nitrogen levels as well as serum CRP levels in the test and placebo arm. The increase in serum insulin level after 4 h was statistically significant in both arms, whereas the insulin level of the placebo and test arm at 4 h was not statistically different. Supplementation showed changes with respect to Archaea and few uncharacterized species but did not show statistically significant variations in microbiome profile at the higher taxonomic levels. A study with large sample size and detailed gut microbiome analysis is warranted to confirm the results statistically as well as to characterize altered species. However, the current study could provide an inkling of a positive alteration in protein digestibility, amino acid absorption, and gut microbiome with regular consumption of protein and enzymes-probiotics blend. Clinical Trial Registration:clinicaltrials.gov/; identifier [CTRI/2021/10/037072].